Anxiety and aggressiveness of adolescents from complete and single-parent families - Ksionda, Olga G.; Bogdanovich, Dina V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The problems of anxiety and aggressiveness in boys and girls from complete and single-parent families are considered. It is revealed that boys are characterised by demonstration of physical aggression. It is determined that girls have more pronounced indicators of situational anxiety, personality anxiety, verbal aggression, indirect aggression, negativism, irritation, resentment, suspicion, guilt, as well as the index of aggressiveness and the index of hostility. It was found that there are no differences in the expression of anxiety in adolescents from complete and single-parent families, while differences in the expression of aggression in the two groups of respondents were found only in the parameter of guilt.
Keywords: adolescence; anxiety; aggressiveness; complete family; single-parent family